Advanced production and operations management - Abante, Marmelo V.; Julianes, Melchor S. (Manila : Unlimited Books Library Services & Publishing Inc., 2024)
"Welcome to the realm of Advanced Production and Operations Management specifically designed for graduate school students! The purpose of this module series is to offer a thorough comprehension of the complexities associated with managing and enhancing business operations in order to address the demands of the current dynamic and competitive business landscape."
Includes references.
English.
Keywords: Production management